PENERAPAN MACAM PEMBERIAN PUPUK DAN DOSIS PUPUK MAJEMUK DALAM PERTUMBUHAN DAN PRODUKSI KACANG TANAH (Arachis hypogaea L.) - Ade Joul Viqqih; Mariyatul Qibtiyah; Istiqomah Istiqomah (Agroteknologi Fakultas Pertanian Universitas Islam Darul 'Ulum (UNISDA), 2022)
One of the problems with growing peanuts is the lack of soil fertility. This is caused by a lack of nutrients in the soil. the effort is to add NPK fertilizer to the soil. The purpose of this study was to determine the effect of different fertilization methods and doses of compound fertilizers. The survey was conducted from February to April 2022 in Takerharjo Village, Solokuro District, Lamongan Regency. This study used a Randomized Block Design (RAK) with two treatment factors namely. Kinds of fertilization, namely. Tugal, Run circle, Kocor. Apply compound fertilizer 200, 250 and 300 kg/ha. Parameters observed included plant height, number of leaves, number of flowers, weight of wet pods, weight of pods per hectare, weight of seeds per plant, and weight of wet stover. So it can be concluded that the combination of circle array treatment and the dose of NPK Mutiara 250 kg/ha has the best effect.